(untitled) (Journal of Civil Engineering Researchers, 2021)
Estimating the amount of alongshore sediment transport (LSTR) is an extremely important task for coastal engineers and coastal project managers to determine the probability of erosion and sedimentation in shores and ports. There are two popular empirical formulas, CERC and Kamphuis, that can be used to calculate the potential of the LSTR rate of the coast. In this study, sediment transport rate was calculated through experimental formulas and effective simulation in the Pozm Harbor is located in Oman Sea in the coordination of 25 ° 21 ° N and 60 ° 17 ° E. Using wave data and Specification of sediment. Also, the numerical simulation of this rate is calculated using numerical modeling. The numerical simulation results behind the groin have been compared with the new hydrography of data was collected in 2017. Furthermore, numerical model has been evaluated and general morphology has been identified. Based on sediment transport volumes calculated at Pozm harbor, a suitable sediment transport rate can be achieved using this numerical model and the Kamphuis formula.